(untitled) (Research, Society and Development, 2022)
This search was developed in theoretical and methodological perspective of ethnomathematics and aims to analyze the measurement methods used by area farmers cubadores land in the municipality of Pacajá - PA compared with the methods of school mathematics. The Ethnomathematics can be used as a tool in the teaching-learning can facilitate inter-relationship between school mathematics and the mathematics used in the daily life of students of the field process. This research had as its theme the scaling of earth, as it is extremely relevant. This theme is part of the daily lives of students and families in the Rural Family House Pacajá. For this survey we used measurement models used by farmers calling themselves cubadores land. From the comparison made between the methods of school mathematics and the methods used by cubadores land came to the conclusion that the mathematics used by them is important not because it approach the math taught in school, but for all the knowledge that was passed to generation to generation and is part of the daily lives of students and their families. It is the knowledge of cubadores of land that should be recognized.